2012
DOI: 10.3329/bmjk.v43i1-2.13015
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of dental caries in the primary dentition among under five children

Abstract: Dental caries is the most important dental health problem in developing countries. 2010; 43 : 7-9

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 5 publications
2
10
0
Order By: Relevance
“…The pooled results of the included studies showed non-significant differences in ECC prevalence between genders, which was consistent with some previous studies 8 9 44 , but contradictory to others 45 46 . According to a meta-analysis of the gender difference in oral health among 5-6-year-olds in South Asia, 3 of 5 ethnic groups showed significantly higher caries prevalence among boys, while 2 groups showed no significant gender difference 47 .…”
Section: Discussionsupporting
confidence: 81%
“…The pooled results of the included studies showed non-significant differences in ECC prevalence between genders, which was consistent with some previous studies 8 9 44 , but contradictory to others 45 46 . According to a meta-analysis of the gender difference in oral health among 5-6-year-olds in South Asia, 3 of 5 ethnic groups showed significantly higher caries prevalence among boys, while 2 groups showed no significant gender difference 47 .…”
Section: Discussionsupporting
confidence: 81%
“…Dental caries is the most prevalent oral health problem in developing countries and affects individuals in all age groups. The prevalence of dental caries among preschool children is high (44.34–66.3%). Moreover, caries often goes untreated in this group, which can lead to different impacts.…”
Section: Introductionmentioning
confidence: 99%
“…11 Another study reported the prevalence of dental caries as 44.34% which was lower. 12 In the present study socio-economic status has influence on the dental caries. It was found that 56.58% participants from the low socio-economic status were affected by multiple teeth (more than three teeth) whereas, only 19.08% participants from the high socio-economic status were affected.…”
Section: Discussionmentioning
confidence: 63%